Osteopetrosis: A Report of Four Cases - Maria Abdulsalam; Iskandar Wahidiyat; Widhodho T. Karyomanggolo; L. A. Tamaela (Indonesian Pediatric Society, 1984)
Four cases of osteopetrosis in infancy had been reported. All cases showed signs of anemia, thrombocytopenia and hepatosplenomegaly which at the beginning suggested the possibility of the diseases more commonly found in our country such as malaria, Cooley anemia, autoimmunne hemolytic anemia and malignancy. The authors then concluded that next to those diseases mentioned above the symptoms and signs of anemia, thrombocytopenia and hepatosplenomegaly especially in infancy should also lead to the possibility of the diagnosis of osteopetrosis. This latter is more obvious when it is accompanied by the difficulty in obtaining the bone marrow specimen.